DEVELOPMENT STRATEGY OF E-LEARNING APPLICATION IN UNIVERSITY DR. SOETOMO USING TECHNOLOGY ACCEPTANCE MODEL 2 (TAM 2) - Irfandi, Bagus; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
University Dr.Soetomo is located in Dr.Soetomo on Semolowaru road location, one of the existing services is e-learning.Based on the result of interview with 31 students, 18 students stated that the application of e-learning application is less interesting and 19 students stated that none of the features available in the e-learning application is good enough.Problem solving solution with Admission Technology Model 2. In this research sampling technique using Slovin theory with 94 respondents.The results can be found.The variables that affect the acceptance, the subjective norm against the image, subjective norms against the accepted use, subjective norms against the use and perception of Ease of Use to the Purpose of Use